Optimasi Lowpass Filter Mikrostrip Frekuensi 10,6 GHz dengan Metode Step-Impedansi - Farida, Fitri (Jurnal Sustainable: Jurnal Hasil Penelitian dan Industri Terapan, 2017)
In the telecommunication process filter is a device that has the function to pass the desired frequency and eliminate / undermine the unwanted frequency. The filter low-pass filter (LPF) is a filter that passes signals with a frequency lower than a certain cutoff frequency and attenuates signals with frequencies higher than the cutoff frequency. The exact frequency response of the filter depends on the filter design. In this paper described the design of low pass filter using the approximation Chebychev with cutoff frequency used is 10.6 GHz because this frequency is the high cutoff frequency in ultra wideband applications. The filter is designed with microstrip technology using step-impedance design method, by combining high impedance microstrip and low impedance microstrip with a certain length. Then design of microstrip filter with step-impedance method and will be done optimization for filter have good characteristic. The filter design uses Roger substrate RT 5880 with dielectric constant (Îµr) = 2,2 with thickness (h) = 0.508. The result obtained in this research is the filter able to pass the lower frequency of cut-off frequency. The results of the filter design simulation have met the expected specification, the return loss value displayed both where the value is smaller than -10 dB and insertion loss value is smaller than -3 dB and has smaller dimensions.